Answers

2015-05-09T21:25:28+05:30
⇒       Using remainder theorem ,factorise: 2 x³ - 13 x ²+ 26 x -15
⇒ Before Factorizing it , let find the value of x in p ( x ), Therefore we get as follows ;-

⇒  p (  x  )  =  2 x
³  –  13 x²   +   26 x  –  15

Now, take x as 1 , we get as ,

⇒ p (  1  )  =  0

Hence we can say that , -   (  x – 1  ) is factor of p  ( x )

 When we divide p( x )  by ( x – 1 ), we get the answer  as (2x² – 11x + 15)

⇒ 2  x³  –  13 x²  +  26 x  –  15  =  ( x  – 1 )(  2 x² – 11 x + 15)

⇒   ( x  –  1 ) ( 2 x²  –  6 x  –  5 x  +  15 )

 ⇒ ( x  –  1 )  [ 2 x ( x  – 3 )  –  5 ( x – 3 )]


 ( x  –  1 )  ( x  –  3 )  ( 2 x  –  5 ) is the answer.


0